Propagation of intense charged-particle beam in coaxial magnetic undulator - Ilyenko, K.; Yatsenko, T. (Вопросы атомной науки и техники, 2013)
The system of dynamics equations describing the propagation of high-current charged-particle beam in a coaxial drift-tube in combined longitudinal homogeneous (guide) and periodic magnetostatic undulator fields is formulated. The self-electric field and both longitudinal and azimuthal components of self-magnetic field of charged-particle beam averaged over the undulator period are obtained. Сформульовано замкнену систему динамічних рівнянь, що описує транспортування пучка заряджених частинок у коаксіальній камері дрейфу в комбінованих скінченому поздовжньому однорідному (ведучому) та періодичному ондуляторному магнітостатичних полях. Отримано вирази для усереднених за періодом ондулятора власних електричних і магнітних полів пучка заряджених частинок у коаксіальній камері дрейфу. Сформулирована замкнутая система динамических уравнений, описывающая транспортировку пучка заряженных частиц в коаксиальной камере дрейфа в комбинированных конечном продольном однородном (ведущем) и периодическом ондуляторном магнитостатических полях. Получены выражения для усредненных по периоду ондулятора собственных электрических и магнитных полей пучка заряженных частиц.